Asymptomatic Plasmodium infection and associated factors among pregnant women in the Merti district, Oromia, Ethiopia. - Bereket Wake Subussa; Teferi Eshetu; Teshome Degefa; Musa Mohammed Ali (PLoS ONE)
Background Asymptomatic Plasmodium infection (API) that occurs during pregnancy increases the risk of stillbirths, abortion, premature delivery, and low birth weight. API also hinders the control and prevention of malaria as infected hosts serve as silent reservoirs for transmission of Plasmodium species in the community. Objective The aim of this study was to determine the prevalence of API and associated factors among pregnant women. This community-based cross-sectional study was conducted at Merti district, Oromia, Ethiopia among 364 pregnant women from March to September 2018. Methods Sociodemographic and obstetrics features were collected using a structured questionnaire. About 2ml of blood was collected from participants to detect Plasmodium species, gametocyte carriage rate, parasite density, and anemia. Results The prevalence of API among pregnant women was 3.6%. The proportion of Plasmodium falciparum and Plasmodium vivax was 6(46.2%) and 7(53.8%) respectively. Out of 13 Plasmodium species identified, Gametocyte carriage rate was 4(30.7%). The geometric mean density of the asexual stage of the parasites was 994.7(interquartile [IQR], 320 to 2200) parasites/ul. The geometric mean gametocyte density was 303.3 (interquartile range [IQR], 160 to 600). The proportion of anemia among Plasmodium-infected participants was 12(92.3%). Previous infection by Plasmodium species (AOR = 5.42; 95% CI: 1.19-29.03, p = 0.047), lack of insecticide-treated bed net use (AOR = 6.52; 95% CI: 1.17-36.44, p = 0.032), and living close to stagnant water (AOR = 4.18; 95% CI (1.12-17.36, p = 0.049) were significantly associated with API. Anemia was significantly higher among Plasmodium-infected than non-infected pregnant women (x2 = 27.62, p <0.001). Conclusion In the current study, a relatively high prevalence of API was detected among pregnant women. Identifying API in the community is important to prevent the unwanted outcomes of Plasmodium infection and its transmission.